Tindak Tutur Asertif Pada Film Sejuta Sayang Untuknya - Reztiana, Mutiara; Umi Diana (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study examines the problem of assertive illocutionary speech acts in the film Sejuta Sayang Untukya by Herwin Novianto. This study aims to describe assertive illocutionary utterances in the film Sejuta Sayang Untuknya by Herwin Novianto. This type of research is descriptive qualitative. The data collection technique in this study utilized the observing method, with the research technique namely basic tapping techniques and advanced techniques which are divided into competent engaged observing techniques (SLC), proficient free engaging observing techniques (SLBC), and note taking techniques. The data research instrument is the researcher himself who acts as an observer. The data analysis technique was carried out by watching the film Sejuta Sayang Untuknya by Herwin Novianto repeatedly in order to understand the meaning of the speech in the film. Then transcribe the data that has been obtained, followed by describing the data. Furthermore, researchers concluded the data that has been analyzed. The results of data analysis are presented in the form of a brief description. This research shows that there are 22 assertive illocutionary speech acts in the film Sejuta Sayang u by Herwin Novianto. These assertive speech acts include: 1) there are 8 assertive utterances of telling, 2) there are 2 assertive utterances stating, 3) there are 8 assertive utterances refusing, 4) there are 3 utterances expressing opinions, and 4) there is 1 assertive utterance reporting.